(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Vision is one of the most crucial human senses since visually impaired people face various challenges due to their inability to move safely in varied environments. This study aims to make it easier for such people to integrate into society by offering a robotic system to help them navigate their interior surroundings. This study aims to develop a smart stick assistant with a camera that can detect and prevent blind individuals from colliding with objects. This project employs GPS for location tracking, an ultrasonic sensor for obstacle detection, and a buzzer and vibrator to alert the user to the presence of an obstacle. When the panic button is touched, the Global System for Mobile (GSM) will alert the guardian of their current location, and the RF remote will locate the blind stick. (Megha N B et al., 2019). The researchers used the Mixed Method to collect significant data to complete this investigation. The engineering method, often known as engineering design, is a systematic approach to solving a problem. Six processes or phases are involved: defining the problem, idea, concept, plan design, and development.